Using extensional flow to reveal diverse aggregation landscapes for three IgG1 molecules. Issue 5 (4th February 2018) - Willis, Leon F.; Kumar, Amit; Dobson, John; Bond, Nicholas J.; Lowe, David; Turner, Richard; Radford, Sheena E.; Kapur, Nikil; Brockwell, David J.
Abstract: Monoclonal antibodies (mAbs) currently dominate the biopharmaceutical sector due to their potency and efficacy against a range of disease targets. These proteinaceous therapeutics are, however, susceptible to unfolding, mis‐folding, and aggregation by environmental perturbations. Aggregation thus poses an enormous challenge to biopharmaceutical development, production, formulation, and storage. Hydrodynamic forces have also been linked to aggregation, but the ability of different flow fields (e.g., shear and extensional flow) to trigger aggregation has remained unclear. To address this question, we previously developed a device that allows the degree of extensional flow to be controlled. Using this device we demonstrated that mAbs are particularly sensitive to the force exerted as a result of this flow‐field. Here, to investigate the utility of this device to bio‐process/biopharmaceutical development, we quantify the effects of the flow field and protein concentration on the aggregation of three mAbs. We show that the response surface of mAbs is distinct from that of bovine serum albumin (BSA) and also that mAbs of similar sequence display diverse sensitivity to hydrodynamic flow. Finally, we show that flow‐induced aggregation of each mAb is ameliorated by different buffers, opening up the possibility of using the device as a formulation tool. Perturbation of the native state by extensional flow may thus allow identification of aggregation‐resistant mAb candidates, their bio‐process parameters and formulation to be optimized earlier in the drug‐discovery pipeline using sub‐milligram quantities of material. Abstract : Hydrodynamic forces are implicated in biopharmaceutical aggregation, yet the ability of different fluid fields (e.g., shear or extensional flow) to trigger aggregation has remained unclear. Here, the authors subject three monoclonal antibodies to defined fluid stresses. The resulting aggregation landscapes reveal that proteins of closely related sequence can have varied aggregation behavior, potentially informing the selection of robust biopharmaceutical candidates, buffers and process conditions which minimise aggregation.